1998
DOI: 10.1111/j.1439-0418.1998.tb01547.x
|View full text |Cite
|
Sign up to set email alerts
|

The side‐effects of pesticides on the egg parasitoid Trichogramma cacoeciae Marchal (Hym., Trichogrammatidae), acute dose‐response and persistence tests

Abstract: The side-effects of 21 pesticides were tested on the Hymenoptera egg parasitoid Trichogramma cacoeciae, using four different types of laboratory methods. The methods combined: (a) adult parasitoid exposure to fresh pesticide residue on glass plates ~ initial toxicity worse case to select harmless preparations, (b) direct spray of host eggs enclosing the parasitoid pupae (less susceptible life stage), (c) duration of harmful activity (persistence) on adultsselect preparations that are less persistent and (d) do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
40
1
11

Year Published

2003
2003
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(59 citation statements)
references
References 2 publications
7
40
1
11
Order By: Relevance
“…Resultados similares foram relatados por Giolo et al (2005a) para captana na mesma concentração testada no presente trabalho, com T. pretiosum. Por outro lado, Hassan et al (1998) obtiveram 49,10% de redução no parasitismo por T. cacoeciae, com o uso de captana 83 W, que foi enquadrado na classe 2 (levemente nocivo). As diferenças obtidas neste caso, provavelmente devem-se à concentração de ingrediente ativo de 5,68 vezes superior à que foi testada no presente estudo.…”
Section: Resultsunclassified
“…Resultados similares foram relatados por Giolo et al (2005a) para captana na mesma concentração testada no presente trabalho, com T. pretiosum. Por outro lado, Hassan et al (1998) obtiveram 49,10% de redução no parasitismo por T. cacoeciae, com o uso de captana 83 W, que foi enquadrado na classe 2 (levemente nocivo). As diferenças obtidas neste caso, provavelmente devem-se à concentração de ingrediente ativo de 5,68 vezes superior à que foi testada no presente estudo.…”
Section: Resultsunclassified
“…De forma similar ao observado no experimento I, Hassan (1994) também obteve para T. cacoeciae a classe 1 com captana (Orthocid 83). No entanto, Hassan et al (1998) obtiveram 49,1% de redução no parasitismo de T. cacoeciae, obtendo a classe 2 para este mesmo ingrediente ativo captana (Captan 83 W). As variações nos resultados provavelmente se devem aos diferentes produtos comerciais usados em diferentes doses e formulações, demonstrando assim a importância sempre da caracterização do pesticida pela sua marca comercial e das características intrínsecas de cada um.…”
Section: Resultsunclassified
“…Overall, the present research has shown that the tested organic treatments are compatible for use in combination with the parasitoid preservation in organic pest management. Even chlorpyrifos was less noxious to T. podisi as compared to other egg parasitoids as Trichogramma pretiosum (BUENO et al, 2008) and T. cacoeciae (HASSAN et al, 1998), for example. It did not reduce adult emergence from sprayed pupae.…”
Section: Discussionmentioning
confidence: 99%